Leukopenia is associated with worse but not prohibitive outcomes following emergent abdominal surgery. Issue 3 (September 2015) - Gulack, Brian C.; Englum, Brian R.; Lo, David D.; Nussbaum, Daniel P.; Keenan, Jeffrey E.; Scarborough, John E.; Shapiro, Mark L.
<x xml:space="preserve">Abstract</x> BACKGROUND There are little data currently available to guide surgical decision making regarding emergent surgical interventions in leukopenic patients. The purpose of this study was to investigate the impact of leukopenia among patients undergoing emergency abdominal operations to better guide preoperative decision making. METHODS The 2005 to 2012 American College of Surgeons' National Surgical Quality Improvement Program database was queried to identify patients who underwent emergent laparotomy. Patients were stratified by preoperative white blood cell (WBC) count (<4.0 × 109/L vs. 4.0–12.0 × 109/L). Baseline demographics, comorbidities, and outcomes were compared. Multivariable logistic regression was performed to estimate the adjusted association between leukopenia and mortality, taking into account the robust array of patient-related factors. RESULTS Of the 20, 443 patients who met study criteria, 2, 057 (8.2%) were leukopenic (WBC < 4.0) before surgery. Unadjusted comparison demonstrated significantly increased major morbidity (45.4% vs. 26.9%, p < 0.001) as well as mortality (24.4% vs. 10.8%, p < 0.001) for patients with leukopenia compared with patients with a normal preoperative WBC count. Only 46.0% (n = 947) of patients with leukopenia before surgery were able to avoid major morbidity or mortality compared with 69.4% (n = 15, 974) of patients with a normal preoperative WBC count (p < 0.001). After multivariable adjustment for patient-related factors, leukopenia was maintained as a significant predictor of mortality. CONCLUSION Although leukopenia remains associated with mortality in patients undergoing emergent laparotomy despite adjustment for other patient-related factors, it is not necessarily prohibitive. Understanding the risk of complications and mortality associated with these procedures is pertinent for preoperative clinical decision making. LEVEL OF EVIDENCE Prognostic and epidemiologic study, level III.